Targeting 8-oxoguanine DNA glycosylase-1 (OGG1) as a therapeutic strategy in inflammatory-related diseases - Samaila, Abdullahi; Basir, Rusliza; Gambo Lawal, Mukhtar; Abas, Razif; Abdullah, Maizaton Atmadini; Abd Majid, Roslaini; Nordin, Norshariza; Hussain, Mohd Khairi; Ab Razak, Nur Izah; Yoke Keong, Yong; Aliyu, Basiru (Taylor & Francis, 2024)
Inflammatory diseases are influenced by oxidative stress. Oxidatively damaged 8-oxoG in DNA is linked to inflammation. The enzyme OGG1 is responsible for repairing the damaged base in the DNA which is linked to pro-inflammatory signaling and severe inflammation. This study aims to explore the potential of targeting OGG1 as a therapeutic strategy in inflammatory disease conditions.